The Effect of Understanding of Tax Regulations and Income Levels on Individual Taxpayer Compliance with Tax Socialization as A Moderation Variable - Rani Setiawati; Henni Rahayu Handayani (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2025)
The study was compiled with the background of the many cases of gratification carried out by state officials, resulting in a phenomenon of public distrust of the government, especially regarding the provisions of tax regulations. The consequences of this phenomenon can cause problems, namely the occurrence of public non-compliance with applicable tax provisions. The study method used is a quantitative method with primary data. The data collection was conducted through the distribution of questionnaires. The results of this research indicate that: (1) the understanding of tax regulations and income levels simultaneously have a positive and significant effect on individual taxpayer compliance at PT INES, (2) the understanding of tax regulations does not have a significant effect on individual taxpayer compliance at PT INES, (3) income levels have a positive and significant effect on individual taxpayer compliance at PT INES,  (4) tax socialization does not moderate the effect of the understanding of tax regulations on individual taxpayer compliance at PT INES, and (5) tax socialization does not moderate the effect of income levels on individual taxpayer compliance at PT INES.